Peran Pancasila dalam Menumbuhkan Kesadaran Nasionalisme dan Patriotisme Generasi Muda di Era Globalisasi - Azzah'ra Syafitri Aulia; Dinie Anggraeni Dewi (Departement of Mathematics Education, 2022)
The current condition, where the rapid flow of globalization and technological progress is increasing so that everything regarding foreign countries will be easily and unlimited.The impact of this current of globalization has caused the fading of the spirit of nationalism and patriotism among the younger generation.Many factors cause the fading of the spirit of nationalism, but one of the biggest is that foreign cultures are more considered modern and according to the times so that they are more likely to like and be interested in the culture of foreign countries.By using a qualitative method with a descriptive approach with data used based on literature studies based on references from previous research on the role of pancasila in growing awareness of the nationalism of the younger generation in the era of globalization.The results obtained in this study, namely Pancasila, play an important role in growing nationalism awareness, because pancasila is the ideology and basis of the state.Pancasila is the basis of all things, so the life of individuals, communities, nations, and countries must be in accordance with ancestral values and values contained in every precept of pancasila.